RI 3366 Mineral Economics Series - 2. Consumption Of Ferrous Scrap And Pig Iron In The United States In 1936 ? Introduction - Robert H. Ridgway (The National Institute for Occupational Safety and Health (NIOSH), 1937)
This paper presents the results of the second in the series of annual canvasses on the consumption of ferrous scrap and pig iron in the United States, inaugurated in 1935 by the Bureau of Mines and published in Report of Investigations 3329. The study was undertaken in response to requests from trade organizations and others for detailed statistics on this phase